2016
DOI: 10.1371/journal.pone.0157648
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 4-Week Training Intervention with Unknown Loads on Power Output Performance and Throwing Velocity in Junior Team Handball Players

Abstract: PurposeTo compare the effect of 4-week unknown vs known loads strength training intervention on power output performance and throwing velocity in junior team handball players.MethodsTwenty-eight junior team-handball players (17.2 ± 0.6 years, 1.79 ± 0.07 m, 75.6 ± 9.4 kg)were divided into two groups (unknown loads: UL; known loads: KL). Both groups performed two sessions weekly consisting of four sets of six repetitions of the bench press throw exercise, using the 30%, 50% and 70% of subjects’ individual 1 rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
1
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 34 publications
0
24
1
2
Order By: Relevance
“…However, this hypothesis was rejected since no significant differences in reliability were observed between the Aver3, Aver4, and MAX procedures. There is not consensus in the scientific literature on which procedure to use for selecting the final throwing velocity outcome with some researchers using the average velocity of several trials [2,[28][29][30], others researchers using the maximum value [3,11,31,32], and others researchers who do not even report the procedure followed to select the final test outcome [2,10,14,22,[33][34][35]. Of note is that this is the first study to compare the reliability of throwing velocity between different procedures commonly used in the scientific literature to select the final test outcome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this hypothesis was rejected since no significant differences in reliability were observed between the Aver3, Aver4, and MAX procedures. There is not consensus in the scientific literature on which procedure to use for selecting the final throwing velocity outcome with some researchers using the average velocity of several trials [2,[28][29][30], others researchers using the maximum value [3,11,31,32], and others researchers who do not even report the procedure followed to select the final test outcome [2,10,14,22,[33][34][35]. Of note is that this is the first study to compare the reliability of throwing velocity between different procedures commonly used in the scientific literature to select the final test outcome.…”
Section: Discussionmentioning
confidence: 99%
“…The diversity in the procedures used to select the final test outcome also compromises the comparison of throwing velocity between different studies. For example, some studies reported the average velocity value of the recorded trials [2,[28][29][30], others the maximum value [3,11,31,32], and others did not specify the procedure used to select the final test outcome [2,10,14,22,[33][34][35]. In relation to this, the average countermovement jump (CMJ) height of several trials has been recommended over the maximum value because it seems to be more sensitive for monitoring the neuromuscular status [36], but not similar analyses have been performed for throwing velocity.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of replenishment training is crucial, seen from the Hungarian data of 2006 issued by National Sports Strategy Sport XXI. (2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015)(2016)(2017)(2018)(2019)(2020) showing that there were 200000 sports people having competition permit in our country, of which 138000 people were from the six popular visual team sport categories (football, handball, basketball, ice hockey, volleyball and waterpolo). The five visual team sports were completed by volleyball from this year (2017).…”
Section: Discussionmentioning
confidence: 94%
“…There are several papers which studied the influence of various types of training on the velocity of the shot in handball over the last ten years, and based on their analyses, we can conclude that a small number of studies focused on a precisely specified set of handball exercises during the experimental training program (Manchado, García-Ruiz, Cortell-Tormo, & Tortosa-Martínez, 2017;Sabido, Hernández-Davó, Botella, & Moya, 2016;Raeder, Fernandez-Fernandez, & Ferrauti, 2015;Hermassi, Van den Tillaar, Khlifa, Chelly & Chamari, 2015;Chelly, Hermassi, Aouadi, & Shephard, 2014;Van den Tillaar & Marques, 2011;Hermassi, Chelly, Tabka, Shephard, & Chamari, 2011;Saeterbakken, Van den Tillаar, & Seiler, 2011;Hermassi, Chelly, Fathloun, & Shephard, 2010;Ettema, Gløsen, & Van den Tillaar, 2008). However, there are no studies which dealt with the influence of a specific training program on the kinematic parameters of the jump shot among elite female handball players.…”
Section: Introductionmentioning
confidence: 99%